Physical, structural, optical and gamma radiation shielding properties of borate glasses containing heavy metals (Bi2O3/MoO3) - Sayyed, M.I.; Kaky, Kawa M.; Gaikwad, D.K.; Agar, O.; Gawai, U.P.; Baki, S.O. (Journal of non-crystalline solids, 2019)
In an attempt to develop a novel gamma radiation shielding glasses, we prepared borate glasses contains a high concentration of heavy metals like Bi2O3 and MoO3 with the composition of 20MoO3-(80-x)B2O3-xBi2O3, were x varied from 30 to 45 mol% using tradition melt-quenching-annealing method. A structural investigation such as XRD and FTIR were characterized to confirm the amorphous structure of the prepared glasses and prove the availability of all chemicals included in these compositions after the melting process. Furthermore, optical studies on these glasses were investigated to prove the transparency of the fabricated glasses. Attenuation characteristics (mass attenuation coefficients, radiation protection efficiency, and half value layer) of the prepared glasses with respect to gamma photons (in the range of 0.356–1.33 MeV) were investigated. The mass attenuation coefficients and radiation protection efficiency results increased with increasing the Bi2O3 content and this improves the attenuation ability for the prepared samples. The radiation protection efficiency also revealed that the glasses have the maximum capability in attenuation gamma photons at 0.356 MeV. The mean free path with the prepared glasses was compared with some concretes which is reported in the literature and with some commercial glasses to assess their potential for use in gamma radiation shielding products.